1996
DOI: 10.1093/infdis/173.4.822
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Immune Globulin on the Prevention of Experimental Hepatitis C Virus Infection

Abstract: The efficacy of postexposure prophylaxis for the prevention of hepatitis C virus (HCV) infection was studied in experimentally infected chimpanzees. Three chimpanzees were inoculated with HCV: Two were treated 1 h later with anti-HCV--negative intravenous immune globulin (IGIV) or hepatitis C immune globulin (HCIG), and a third animal was not treated. HCV infection was detected in all 3 animals within a few days of inoculation. Once passively transferred anti-HCV declined in the HCIG-treated animal, there was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
94
1
1

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 176 publications
(99 citation statements)
references
References 26 publications
3
94
1
1
Order By: Relevance
“…Hepatitis B immunoglobulin prepared before the elimination of antibody to HCV ϩ blood donors appeared to protect French patients who underwent transplantation for HBV and HCV coinfection from recurrent HCV infection. 2,79 It was postulated that these immunoglobulin preparations contained large amounts of polyclonal HCV antienvelope antibodies, capable of neutralizing residual circulating HCV, thereby preventing HCV infection of the graft. Subsequent chimpanzee studies conducted at the Centers for Disease Control and Prevention have shown that a single dose of postexposure hepatitis C immunoglobulin (HCIG; prepared from HCV RNA ϩ donors) markedly prolonged the incubation period of acute HCV, whereas repeated doses reduced viremia levels in chronic infection.…”
Section: Posttransplantation Prophylaxismentioning
confidence: 99%
“…Hepatitis B immunoglobulin prepared before the elimination of antibody to HCV ϩ blood donors appeared to protect French patients who underwent transplantation for HBV and HCV coinfection from recurrent HCV infection. 2,79 It was postulated that these immunoglobulin preparations contained large amounts of polyclonal HCV antienvelope antibodies, capable of neutralizing residual circulating HCV, thereby preventing HCV infection of the graft. Subsequent chimpanzee studies conducted at the Centers for Disease Control and Prevention have shown that a single dose of postexposure hepatitis C immunoglobulin (HCIG; prepared from HCV RNA ϩ donors) markedly prolonged the incubation period of acute HCV, whereas repeated doses reduced viremia levels in chronic infection.…”
Section: Posttransplantation Prophylaxismentioning
confidence: 99%
“…[5][6][7][8][9][10][11] Studies in chimpanzees have revealed that antibody neutralization of HCV is not easily attained. 12,13 Recently, Cooper et al observed that strong antibody responses to HCV proteins were not necessary for viral clearance in HCV-inoculated chimpanzees. 14 Several investigators have also observed that circulating HCV-specific antibodies do not prevent reinfection of chimpanzees with HCV.…”
mentioning
confidence: 99%
“…In humans, it has been shown that nonspecific immunoglobulins (Igs) have some prophylactic effects on hepatitis C. [4][5][6] In chimpanzees, passive immunization with Ig preparations prolonged the incubation period of acute hepatitis C, and HCV infection was prevented after in vitro neutralization with plasma of a chronically infected patient. 7,8 Although it appears that the effects of passive immunization are limited and complete clearance of HCV is not usually accomplished, vaccination experiments have been more successful. When vaccinated with recombinant envelope proteins, chimpanzees developed high serum titers of anti-E2 protein (envelope-2 glycoprotein) antibodies and were protected from subsequent challenge with homologous isolates.…”
mentioning
confidence: 99%